Cycle parametric study on the performance of aeroderivative gas turbine models developed from a high bypass turbofan engine. Issue 1 (1st January 2017) - Effiom, Samuel O.; Abam, Fidelis I.; Nwankwojike, Brethrand N.
Abstract: Cycle parametric study on the performance of various aeroderivative gas turbine models is presented. This was carried out to investigate the standard features that maximizes the performance of these turbines. The gas turbine models investigated were: Gas turbine model (GT) with LP compressor zero-staging, GT with intercooling, GT with reheating between high pressure (HP) turbine and low pressure (LP) turbine or LP turbine and free power (FP) turbine, and a GT with a combination of intercooling, reheating and recuperation. Turbomatch simulation codes were used to develop the models. Results showed that adding two zero-stages to the LP compressor increased overall pressure ratio (OPR), combustor outlet temperature (COT) and air flow rate by 36, 13, and 31.4% respectively. Also, specific fuel consumption (SFC) reduced by 12.6% while shaft power, thermal efficiency and specific power improved by 49.6% (from 38.4 to 42.3% efficiency), 11.11 and 36.5% respectively. This becomes a standard feature to be installed on all aeroderivative GT models. Modelling the GT with an intercooling exit temperature of 320 K further increased power output by 39%. Having the reheat combustor between the HP turbine and the LP turbine gave the best reheating option with a COT of 1544.27 K, OPR of 31.15 and 2–3% increase in thermal efficiency. Combination of intercooling and recuperation with 90% effectiveness resulted in T HPC, exit < T exhaust that led to higher efficiency at low OPRs.